Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Video Dalam Meningkatkan Hasil Belajar Siswa - Amarani, Shaqila Eka Putri; Sartika, Sri Hardianti; Sadiah, Ati (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The problem in this study is the low learning outcomes of students. The purpose of this study was to improve the learning outcomes of students in economic subjects by using the Problem Based Learning learning model assisted by Video Media in improving Student Learning Outcomes (Quasi Experiment on Economics Class XI SMA Negeri 10 Tasikmalaya). The method used is quasi experiment with research design The Nonequivalent Control Group Design. The population in this study were classes XI-8, XI-9 and XI-10, XI-11, XI-12 and the research sample used was 2 classes. The samples in this study were class XI-8 as the experimental class and XI-10 as the control class with nonprobability sampling with purposive sampling type. Based on the results of the study, it explains that there is a significant difference in improving student learning outcomes by using the Problem Based Learning learning model with video media assistance on labor material, where the average posttest value is superior to the average posttest using the Problem Based Learning learning model with video media assistance, thus it can be concluded that the Problem Based Learning learning model with video media assistance can improve student learning outcomes.